ANALISIS STRUKTUR GERAK TARI INDANG TAGAK MINANG SAIYO JORONG SAMPU NAGARI LUBUK GADANG UTARA KECAMATAN SANGIR KABUPATEN SOLOK SELATAN - Mia Shella Agusty, Mia Shella Agusty Mia Shella Agusty; Asriati, Afifah (SENDRATASIK UNP, 2019)
AbstractÂ This study aims to analyze and describe the motion structure of the Indang Tagak Minang Saiyo dance in Jorong Sampu Nagari Lubuk Gadang Utara Sangir District, Solok Selatan Regency.This type of research was a qualitative research with using a descriptive approach. The main instrument in this study was the researcher and was assisted by supporting instruments such as stationery, photo camera and video camera. The type of data used primary and secondary data. Techniques of Data collection were carried out by taking literature study, observation, interviews and documentation. The steps in analyzing data were done by collecting, reducting, presenting and drawing data conclusions. The result shows that the motion structure of Indang Tagak Minang Saiyo Dance in Jorong Sampu Nagari Lubuk Gadang Utara Sangir District, Solok Selatan Regency is consisted of 66elements of kinem, 33 elements of morphokinem, 16 elements ofmotif, 7 elements of provision and one is a whole dance form, namely Indang Tagak Minang Saiyo Dance. The hierarchical relationship system consists of five levels, namely kinem, morphokinem, motif, provision and a whole dance. Whereas, the relationships system that are contained in this dance are the Syntagmatic and Paradigmatic relationships.Â Keywords: analysis, motion structure, indang tagak minang dance